2017
DOI: 10.1155/2017/3096917
|View full text |Cite
|
Sign up to set email alerts
|

K-Line Patterns’ Predictive Power Analysis Using the Methods of Similarity Match and Clustering

Abstract: Stock price prediction based on K-line patterns is the essence of candlestick technical analysis. However, there are some disputes on whether the K-line patterns have predictive power in academia. To help resolve the debate, this paper uses the data mining methods of pattern recognition, pattern clustering, and pattern knowledge mining to research the predictive power of K-line patterns. The similarity match model and nearest neighbor-clustering algorithm are proposed for solving the problem of similarity matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Candlestick charts are a form of technical analysis visualization that are created by plotting the opening, highest, lowest, and closing prices of each analysis period [15]. Figure 1 represents an example of a candlestick chart.…”
Section: Candlestick Patterns Analysismentioning
confidence: 99%
“…Candlestick charts are a form of technical analysis visualization that are created by plotting the opening, highest, lowest, and closing prices of each analysis period [15]. Figure 1 represents an example of a candlestick chart.…”
Section: Candlestick Patterns Analysismentioning
confidence: 99%
“…Statistical results revealed that four patterns were profitable for the Taiwan stock market after transaction costs [14]. Lv et al testing the predictive power of the Three Inside Up pattern and Three Inside Down pattern with the testing dataset of the K-line series data of Shanghai 180 index component stocks over the latest 10 years [15].…”
Section: Introductionmentioning
confidence: 99%
“…In [19], the author used multiresolution analysis techniques to predict the interest rate next-day variation. Using K-line patterns' predictive power analysis, Tao et al [20] found that their proposed approach can effectively improve prediction accuracy for stock price direction and reduce forecast error.…”
Section: Introductionmentioning
confidence: 99%